Students’ Reception of Intrinsic Elements and Moral Values in Hans Christian Andersen’s The Ugly Duckling - Tri Jampi Setiyorini; Ape Segenil (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines students’ reception of the intrinsic elements, moral values, and impressions of Hans Christian Andersen’s short story The Ugly Duckling. The study responds to the need for literary learning that not only identifies textual elements but also explores how students interpret moral meaning through reader response. A descriptive qualitative design was employed. The participants were 27 second-semester students from class B of the English Education Department at Universitas Muhammadiyah Purworejo in the 2025/2026 academic year. Data were collected from February 24 to March 10, 2026, through semi-structured interviews and document analysis. The interview data were transcribed, coded, and interpreted, while the document analysis was used to support the interpretation of intrinsic elements in the short story. The findings show that students identified four main themes: bullying, discrimination, hardiness, and the search for self-identity. The main characters identified were the ugly duckling, the mother duck, and the ugly duckling’s siblings. Students also recognized several messages, including not judging people by appearance, appreciating differences, avoiding bullying and discrimination, maintaining confidence, being patient, and never giving up. The moral values found in the story were patience, empathy, care, tolerance, justice, and struggle. Students were impressed by the ugly duckling’s patience, persistence, and refusal to take revenge. The study implies that The Ugly Duckling can be used as a meaningful literary text to support character education and moral reflection in English literature learning.